COPING WITH FOURTH INDUSTRIAL REVOLUTION CHALLENGES: LEADERSHIP COMPETENCIES IN THE AIRLINE INDUSTRY - Garcia, Edmond Paolo (Jurnal Manajemen dan Kewirausahaan, 2024)
This study aimed to identify leadership competencies crucial for navigating the Fourth Industrial Revolution in the airline sector, utilizing a mixed-method approach, specifically an explanatory sequential design. Data from 210 employees underwent analysis using descriptive and inferential statistics, predictive analytics, and bootstrapping methods. Findings indicated that while age and education had no bearing on leadership competencies, gender, tenure, and positions displayed variations, indicating competency enhancements regardless of demographics. Furthermore, all competencies studied significantly predicted overall success, with some explicitly influencing challenges associated with the Fourth Industrial Revolution. A proposed leadership development framework addressed the findings precisely challenges, with practical implications focusing on driving success and sustainability in the airline industry.